BS IEC 61937-11 AMD2. Digital audio. Interface for non-linear PCM encoded audio bitstreams applying IEC 60958. Part 11. MPEG-4 AAC and its extensions in LATM/LOAS (TA 20) (5th June 2020) - British Standards Institution,
No abstract available